Challenges in Elder Care - Zawada, Edward T. Jr (IntechOpen, 2016)
This work is intended as a brief but focused compilation to assist with diagnosis and management of the most common serious medical problems in the rapidly growing geriatric population. The geriatric population recently expanded by the fact that the baby boomers have reached the milestone of 65 years of age in the past 5 years. Tips for diagnosis, medication administration, and logistics of cost-effective management in the health-care continuum are presented in this book. The latter often consists of a journey from home to medical office to emergency room to hospital bed to intensive care unit to long-term acute care hospital to skilled nursing facility to long-term residential facility and/or back home, which is also reviewed in the book Geriatrics.